2014
DOI: 10.1039/c4ce01242a
|View full text |Cite
|
Sign up to set email alerts
|

Facile growth of hollow porous NiO microspheres assembled from nanosheet building blocks and their high performance as a supercapacitor electrode

Abstract: Self-assembled hollow flowerlike NiO as a promising supercapacitor material has been fabricated by a facile hydrothermal process and the formation mechanism of the flowerlike morphology is investigated.The structure and morphology of the NiO samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) etc. and the surface area of the NiO sample was analyzed by measuring its N 2 adsorption-desorption isotherms. The results indicated that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 34 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…Generally, transition metal (Ru, Mn, Ni, Co, and V) oxides have been http://dx.doi.org/10.1016/j.colsurfa.2015.06.040 0927-7757/© 2015 Elsevier B.V. All rights reserved. employed as pseudocapacitor electrodes and have shown good pseudocapacitive performances [3][4][5][6][7][8][9]. Moreover, it has been found that the electrochemical performances of the electrode materials are strongly dependent on their sizes, morphologies and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, transition metal (Ru, Mn, Ni, Co, and V) oxides have been http://dx.doi.org/10.1016/j.colsurfa.2015.06.040 0927-7757/© 2015 Elsevier B.V. All rights reserved. employed as pseudocapacitor electrodes and have shown good pseudocapacitive performances [3][4][5][6][7][8][9]. Moreover, it has been found that the electrochemical performances of the electrode materials are strongly dependent on their sizes, morphologies and structures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a hollow porous flowerlike NiO nanostructure was synthesized by a hydrothermal process displays superior capacitive performance with large capacitance of 619 F g -1 at 5 mA cm -2 [13] ; The direct growth of uniform NiO nanoparticles on different substrates exhibit the high specific capacitance of 1386 F g -1 at 1 A g -1 [14] ; The fabrication of 1D…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The hierarchical structure promotes contact at the electrode/electrolyte interface and provides more active sites for the oxidation–reduction reaction. Moreover, Fan et al44 compounded NiO precursors by a simple hydrothermal method, and then constructed hollow flower‐like NiO by self‐assembly. Electrochemical performance tests revealed that this NiO electrode material had good electrochemical reversibility with a capacitance of 619 F g −1 and retained outstanding cycling performance after 1000 cycles.…”
Section: Nanostructure Design For Constructing High‐performance Nickementioning
confidence: 99%